2022
DOI: 10.3389/fmicb.2022.1031079
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut fungi in systemic lupus erythematosus – A pilot study

Abstract: ObjectiveGut fungi, as symbiosis with the human gastrointestinal tract, may regulate physiology via multiple interactions with host cells. The plausible role of fungi in systemic lupus erythematosus (SLE) is far from clear and need to be explored.MethodsA total of 64 subjects were recruited, including SLE, rheumatoid arthritis (RA), undifferentiated connective tissue diseases (UCTDs) patients and healthy controls (HCs). Fecal samples of subjects were collected. Gut fungi and bacteria were detected by ITS seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…After evaluating the 15 clinical studies using the Newcastle–Ottawa scale [ 23 ], five (5/14) clinical studies [ 26 , 27 , 32 , 34 , 39 ] were rated with a score of 7, eight (8/15) [ 25 , 28–31 , 33 , 35 , 38 ]with a score of 6, and two (2/15) [ 36 , 37 ] with a score of 5, indicating that the overall quality of the included studies was universally high ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After evaluating the 15 clinical studies using the Newcastle–Ottawa scale [ 23 ], five (5/14) clinical studies [ 26 , 27 , 32 , 34 , 39 ] were rated with a score of 7, eight (8/15) [ 25 , 28–31 , 33 , 35 , 38 ]with a score of 6, and two (2/15) [ 36 , 37 ] with a score of 5, indicating that the overall quality of the included studies was universally high ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In eight (8/15) of the clinical studies, alpha diversity was found to be lower in LN patients than in HCs, mainly by the Chao1 [ 25 , 36 , 37 , 39 ], Shannon indexes [ 26 , 28 , 33 , 35 , 37 , 39 ] and Simpson indexes [ 26 ] and in three (3/15) clinical studies [ 31 , 32 , 45 ], no significant differences were found. In terms of beta diversity, seven (7/15) clinical studies [ 25 , 26 , 28 , 30 , 31 , 33 , 39 ] found that there was a difference in the diversity between the two groups, while four (4/15) clinical studies [27, 32 , 36 , 37 ] reported no significant difference ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to bacteria that can influence various physiopathological processes from immune development to phenotype, mounting studies demonstrated the involvement of intestinal fungi in the regulation of immune homeostasis ( Doron et al, 2021 ; Li B. Z. et al, 2022 ).…”
Section: Fungi and Psoriasismentioning
confidence: 99%